Research into the importance of small seaport nautical infrastructure in the development of the local economy - Nowaczyk, Piotr (Badania nad znaczeniem infrastruktury żeglarskiej małych portów morskich w rozwoju lokalnej gospodarki, 2019)
Research into the importance of small seaports in the development of the local economy is extremely rare. This applies equally to the assessment of port infrastructure. Considering the research deficiencies, the decision was made for this paper to assess the importance of nautical infrastructure to port operators and the local economy. The territorial scope of the research covers seven small ports where the vast majority of national maritime sailing is concentrated. The importance of nautical infrastructure to port operators was assessed based on a cost-benefit approach. However, in the case of the local economy, the benefits of the expansion of the nautical infrastructure were determined based on the sailors’ spending, accounting for cash flows and multiplier effects. The study was based on available statistical data and the results of surveys and interviews. The studies carried out showed a negative return on nautical investments for port operators. However, nautical facilities generate net benefits to the local economy. The importance of nautical investments for port municipalities requires further research, especially into cash flows and the indirect and induced effects
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 90-101
Keywords: nautical infrastructure; small seaports; local development; research methods; infrastruktura żeglarska; małe porty morskie; rozwój lokalny; metody badań